2018
DOI: 10.1002/14651858.cd012779.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic platelet transfusions prior to surgery for people with a low platelet count

Abstract: Findings of this review were based on three small trials involving minor surgery in adults with thrombocytopenia. We found insufficient evidence to recommend the administration of preprocedure prophylactic platelet transfusions in this situation with a lack of evidence that transfusion resulted in a reduction in postoperative bleeding or all-cause mortality. The small number of trials meeting the inclusion criteria and the limitation in reported outcomes across the trials precluded meta-analysis for most outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 79 publications
1
31
0
1
Order By: Relevance
“…fever or infection) (Webert, Cook, Sigouin, Rebulla, & Heddle, ). Our findings were similar to a recent Cochrane review that found insufficient evidence to recommend prophylactic platelet transfusion and no evidence that transfusion resulted in a reduction in POB for minor surgical procedures (Estcourt et al., ).…”
Section: Discussionsupporting
confidence: 90%
“…fever or infection) (Webert, Cook, Sigouin, Rebulla, & Heddle, ). Our findings were similar to a recent Cochrane review that found insufficient evidence to recommend prophylactic platelet transfusion and no evidence that transfusion resulted in a reduction in POB for minor surgical procedures (Estcourt et al., ).…”
Section: Discussionsupporting
confidence: 90%
“…A Cochrane systematic review identified two studies that assessed the use of platelet transfusions in patients undergoing minor procedures (►Table 5). 77 The first study compared the use of platelet transfusions or plasma transfusions or both to desmopressin in adults with chronic liver disease undergoing dental extraction. 78 There was no evidence of a difference in minor or major bleeding; however, the study only included 36 participants in the analysis.…”
Section: Other Surgery or Procedures With A Lower Risk Of Bleedingmentioning
confidence: 99%
“…To prevent excess bleeding, guidelines recommend platelet transfusions prior to surgery for patients with counts <50 × 10 9 /L . Avatrombopag and lusutrombopag work to increase platelets, and it is therefore unsurprising that administering these drugs led to fewer transfusions.…”
Section: Avatrombopag and Lusutrombopagmentioning
confidence: 99%